Dignity of life: Moral philosophy, organisational theory, and hostage rescue - Avichal (New Delhi I K International, 2023)
Scholarly, multidisciplinary, and iconoclastic, this book provides a comprehensive study of human behaviour in organisational setting, discusses the theory and principles of self-organisation, elaborates the strengths of self-organisation over command organisation, and gives a complete roadmap to set up and sustain in any culture and society an exceptionally capable hostage rescue force specialising in mass hostage rescue. However, its numerous valuable insights, relying not on technology but people and employing the force of their intrinsic motivation, are not relevant to the niche of special forces and wider military context alone but can be employed across all occupational settings to build highly efficient organisations where people work voluntarily and deliver responsibly without the supervision and control of command element. Beyond formal organisations, all fields of human activities, including the private lives of individuals too can immensely benefit from radical ideas and useful information contained in it.
Keywords: Human Behaviour; Moral Philosophy; Self-Organisation